Analisis Laporan Keuangan Untuk Mengatur Kinerja Keuangan Dengan Rasio Keuangan (Pada PT Unilever Indonesia Tbk Periode 2018-2021) - Lala Rusianah; Hurriyaturrohman Hurriyaturrohman (Komunitas Dosen Indonesia, 2024)
This study aims to analyze the this study aims to analyze the financial performance of PT Unilever Indonesia Tbk. by using financial ratio. The research method used is quantitative descriptive, the data source is secondary data. The data collection technique was carried out using a documentation technique in the form of PT Unilever Indonesia’s financial statement from 2018 to 2021, which was measured using financial ratio, consisting of: liquidity ratio, solvency ratio, profitability ratio, and activity ratio. The data analysis method in this study is a descriptive analysis method by collecting, processing, and analyzing existing data to provide an overview of the conditions under study. Based on the result of research and analysis that has been carried out, financial performance at PT Unilever Indonesia Tbk. is measured using (1) Liquidity ratio, consisting of: current ratio, quick ratio, cash ratio, cash turnover ratio, and net working capital stock ratio, it can be concluded as a whole that its financial performance is declared “Not Good”. (2) Solvency ratio, consisting of: the ratio of debt to assets and debt to equity can be concluded as a whole that its financial performance is declared “Not Good”. (3) Profitability ratio, consisting of: return on investment ratios, return on equity ratios, gross profit margins, and net profit margins, it can be concluded as a whole that the financial performance is declared “Good”. (4) Activity ratio, consisting of: total assets turnover ratio, and fixed assets turnover ratio, it can be concluded that the overall financial performance is stated to be “Good”.